ANALISIS METAFORIS DALAM LIRIK LAGU GALLAGHER BROTHERS: STUDI SEMANTIK: Metaphorical Analysis in the Song Lyrics - lingga, thomson (ELATICS JOURNAL, 2024)
The study, entitled "A Metaphorical Analysis in The Song Lyrics of The Gallagher Brothers" aims to find the most frequent metaphor kinds in the selected song lyrics. The meaning of the metaphor is mostly found in literary works as portraits of human social life. This study therefore aims to identify the types of metaphor used and to find the meaning of metaphor in The Gallagher Brothers song lyrics. The study applied descriptive study accurately and systematically describes phrases and sentences in the song lyrics through the theory of Lakoff and Johnson (1980) about metaphor conceptual to identify kinds of metaphors and to determine the target and source of each datum found. The data sources were taken from the selected songs of the Gallagher brothers. The findings of this study showed that 20 expressions classified into ontological metaphors are mostly found in two others, orientational and structural metaphors. Otherwise, the meaning of data selected in the song lyrics is varied and easier to understand by using the theory to analyse. Keywords: Metaphoric Meaning; Source Domain; Target Domain; Song Lyrics.